Critical Foundation in the Book "Contemporary Arabic Poetry: Its Issues and Technical Aspects", By Dr. "Izzuldin Ismaiel" - Farouk Maghrebi (دراسات في اللغة العربيّة وآدابها)
Studying the critical thinking of critics, though plentiful, is not enoughyeto Such study offers the reader the course followed by the critic and his starting points of literary vision. Critic Izzuldin Ismaiel has produced a big volume of work. He is one of the pioneers that played a prominent role in featuring the modern poetic verse in Egypt and other Arab countries. His Book "Contemporary Arabic Poetry: Its Issues and Technical Aspects", though old, is still considered the constitution that outlines this movement. This Research discusses this ideas of the critic in his book, endorsing some and disagreehng with others. The critic has presented a description of Modern Poetic movement both in its topics and in techniques. There has been some disagreement with this scholar on some cases but this is something normal as the passage of time make it inevitable.